APPLICATION OF SOFTWARE DEFINED RADIO FOR RADIO EMISSION SOURCE DIRECTION FINDING AND TRACKIN - Shcherbyna, Olga; Katushonok, Fedir; Zadorozhnyi, Oleksandr (Science-based technologies, 2025)
Recently, accurate positioning of objects in space has gained significant importance, encompassing various fields, both civil and military. The position of a radio emission source (RES) can be static or dynamic, single or multi-position, friendly or hostile. The function of detecting and tracking a radio signal source (direction finding function) is often the most critical component of modern radio systems and complexes for detection, ranging, monitoring, navigation, control, and communication. The performance of these systems directly depends on the quality characteristics of the direction-finding part. Among the main characteristics of such systems are the operating frequency range, direction-finding accuracy, and the range of angles for unambiguous measurements, which require particularly high standards, especially when applying direction finding for unmanned aerial vehicle (UAV) systems. Software-defined radio (SDR) is a radio device in which most physical functions are implemented in software, and hardware functions are quickly modified according to the requirements of the communication standard. Due to the software implementation of most high-frequency signal processing functions and flexible software control, SDR provides significant enhancement of functional capabilities by operating in a wide frequency range and for various communication standards. The SDR device is known for its flexible configuration, accessibility, and speed, and is often used for various tasks in research and signal processing of radio communication, for example, communication network research, data telemetry programs, and angle of arrival (AoA) measurement programs. Combining antenna arrays with SDR technology allows for the implementation of adaptive antenna systems with digital signal processing that can effectively analyze the interference environment and manage radiation pattern of an antenna array to improve user interaction while simultaneously suppressing unwanted interference sources. This combination enables the rapid calculation of weighting coefficients based on data about the angular position of the sources of useful signals and interference signals, thereby improving communication quality and suppressing unwanted interference sources.